Pozycja Polski na arenie międzynarodowej jako wynik celowych działań komunikacyjnych - Daszkiewicz, Magdalena; Waniowski, Paweł (International Position of Poland as a Result of Communication Activities, 2007)
Building a favourable image is one of the ways of creating competitive advantage of the country. To successfully manage the process of image formation Poland must conduct coordinated and long-term communication activities. In the article we describe key areas and factors influencing perception of our country. We took into consideration among other things elements of identity, main communication activities and institutions responsible for the image of Poland. The article presents also issues concerning the image of Wroclaw, as the example of the relationship between regional promotional activities and country's international position.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 15-27